Legislation and environmental policy in Brazil: the possibilities of sustainable development and the risks of environmental retrogression - Vilani, Rodrigo Machado (Revista Brasileira de Pós-Graduação, 2014)
The objective of this study is to analyse the appropriation of the sustainable development ideal by major Brazilian federal environmental regulations. Criticised for being broad and vague, the concept of sustainable development strengthened during the Rio+20 conference contains a commitment to intragenerational balance and intergenerational equity also upheld by the Federal Constitution. Therefore, it is important to recognise the directions given by legislation to define the compatibility of social, environmental and economic aspects. We opted for qualitative, bibliographic and normative research in order to circumscribe the conceptual aspects and constitutional limitations of the term, taking into account legislation and federal policy developments. We conclude with general and specific considerations in order to contribute to the adequacy of the current norms and public policies designed to ensure the rights of future generations.